Design, Synthesis, and Applications 2004
DOI: 10.1115/nano2004-46016
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting Membrane Proteins Into Artificial Membranes and Detection of Their Activities

Abstract: We have successfully purified BR from purple membrane of Halobacterium Salinarium and Cox from the genetically engineered plasmid inserted in Rhodobacter Sphaeroides. The activities of the purified enzymes have shown in lipid vesicles as well as in polymer vesicles and planar membranes. Phosphatidylcholine derived lipid vesicles created the most nature like environment for the enzymes. Triblock copolymer membrane was the alternative choice for membrane protein reconstitution since polymers are more durable, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Furthermore, upon the incubation of BR-functionalized proteopolymersomes with green light in low surrounding pH conditions (3.0), it was observed that the pH level within the polymeric vesicle increased, indicating a net outward flow of protons due to an achieved 'physiological' orientation of the protein (figure 5). This pH-induced orientation of BR has been previously shown to be due to a modified surface polarity of the membrane that favours the physiological orientation of the protein [19,39]. This orientation is noted in the negative pH change with respects to the internal pH of the vesicle, signalling an outward flow of protons.…”
Section: Analysis Of Br-dependent Gradient Generationmentioning
confidence: 78%
See 4 more Smart Citations
“…Furthermore, upon the incubation of BR-functionalized proteopolymersomes with green light in low surrounding pH conditions (3.0), it was observed that the pH level within the polymeric vesicle increased, indicating a net outward flow of protons due to an achieved 'physiological' orientation of the protein (figure 5). This pH-induced orientation of BR has been previously shown to be due to a modified surface polarity of the membrane that favours the physiological orientation of the protein [19,39]. This orientation is noted in the negative pH change with respects to the internal pH of the vesicle, signalling an outward flow of protons.…”
Section: Analysis Of Br-dependent Gradient Generationmentioning
confidence: 78%
“…This culture broth was spun down in a Beckman JLA 9.1 rotor at 8000 rpm for 30 min to produce cell pellets. Pellets were re-suspended in 4.2 mM MgSO 4 solution with 0.1 mg ml −1 DNase I and stirred for 24 h at A depiction of the vesicle assembly is shown here as described in [6,19]. Bacteriorhodopsin (BR) is the element that confers light-dependence upon the system.…”
Section: Protein Purificationmentioning
confidence: 99%
See 3 more Smart Citations